1971
DOI: 10.1002/j.2050-0416.1971.tb03404.x
|View full text |Cite
|
Sign up to set email alerts
|

DISCOVERY OF THE “CIDER SICKNESS” BACTERIUMZYMOMONAS ANAEROBIAIN APPLE PULP

Abstract: After a lapse of nearly 20 years the "cider sickness" organism has been re discovered. On this occasion it was found in apple pulp, this being the first time it has been isolated from a source other than "sick cider". In spite of its presence in the pulp, no outbreak of the disorder occurred in the factory from which it was isolated, thus reaffirming the soundness of the cider-making methods specifically designed to prevent the growth of this bacterium. The characteristics of this isolate are compared with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1972
1972
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…The remaining 23 strains were acid-tolerant, Gram negative bacteria belonging to other groups. After further tests, 1 of these non-acetifying strains proved to be a strain of the cider spoilage organism Zymomonas anaerobia (Carr & Passmore, 1971). The 22 other strains were identified to generic level and these organisms will be the subject of a later paper.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining 23 strains were acid-tolerant, Gram negative bacteria belonging to other groups. After further tests, 1 of these non-acetifying strains proved to be a strain of the cider spoilage organism Zymomonas anaerobia (Carr & Passmore, 1971). The 22 other strains were identified to generic level and these organisms will be the subject of a later paper.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been isolated from spoiled beers in England 5 . Z. mobilis pomaceae was isolated in England from sick cider 3,14 and apple pulp 4 . No differences in the 16S rDNA sequences were observed between Zymomonas mobilis mobilis phenotypic centrotype strain ATCC 29191 and Zymomonas mobilis pomaceae type strain ATCC 29192, while 20 differences were observed between the Z. mobilis AN 0101 sequence and the sequences of the previously mentioned strains.…”
Section: Identification Of Bacteriamentioning
confidence: 99%
“…Reduction of quinic and shikimic acids to dihydroshikimic acid by a heterofermentative Lactobacillus sp. (Carr & Whiting 1971). Leifson (1954) had shown that the genus Acetobucter was not homogeneous.…”
Section: A C E T I C a C I D B A C T L R I Amentioning
confidence: 99%
“…It is the accumulation of acetaldehyde that causes this organism to produce a fruity off-flavour and, when in combination with phenolic juice components, a dense turbidity. A major outbreak of 'cider sickness' has not occurred for a considerable time and it was therefore notable when a strain was isolated by Dr Passmore during her search for strains of acetic acid bacteria (Carr & Passmore 1971). It was isolated from commercial apple pulp and although we warned the cider maker of the possibility of 'cider sickness', the disorder never occured.…”
Section: Z Y M O M O N a Smentioning
confidence: 99%